Maternal neglect results in reduced telomerase activity and increased oxidative load in rats. (4th May 2021) - Sarıbal, Devrim; Kireçtepe Aydın, Aslı; Kılıç, Mahmut Alp; Shakil, Faariah; Balkaya, Mustafa
Abstract: A growing number of studies in humans have linked chronic stress, particularly during early life, to telomere shortening and increased oxidative stress. The effect of stress on telomerase activity, however, is understudied. Given the importance of telomere attrition in a wide range of diseases and immunosenescence, further research to elucidate the mechanisms by which stress alters telomere dynamics is required. However, animal studies are lacking, and it is not clear whether widely used stress models reliably mimic the accelerated telomere shortening observed humans. To this end, we evaluated the effect of maternal separation with early weaning (MSEW) on telomere length, telomerase activity, and oxidative load in rats. A total of 45 animals were used, (17 control: 3 males and 11 females and 28 MSEW: 11 males, 17 females), which were then sacrificed one year after birth. Importantly, we determined that telomerase activity measured in plasma was significantly decreased in the MSEW group, along with a non-significant reduction in telomere length from whole blood cells. We also examined the levels of three oxidative markers: plasma malondialdehyde, glutathione in erythrocytes, and plasma catalase activity. Malondialdehyde was found to be elevated in the plasma, indicating increased lipid peroxidation. Interestingly, while the antioxidant glutathione was upregulated, catalase activity remained unchanged. Our findings indicate that the rat MSEW model induces chronic changes to telomere dynamics and oxidative load and can capitulate long term aspects of human childhood stress.